Parental impact on adherence of young children to 24-h movement behaviour guidelines: the Czech FAMIly Physical Activity, Sedentary behaviour and Sleep study - Sigmundová, Dagmar; Vorlíček, Michal; Voráčová, Jaroslava; Dygrýn, Jan; Sigmund, Erik (European journal of public health, 2025)
Human movement behaviour typically unfolds in 24-h cycles, with children being additionally influenced by their parents. Therefore, the aim of this study was to investigate the adherence of 3-10-year-old children to the World Health Organization's (WHO) 24-h movement behaviour guidelines in relation to the behaviours of their mothers/fathers. Data from the Czech cross-sectional FAMIly Physical Activity, Sedentary behaviour and Sleep study included 381 families (with at least one child aged 3-10 years) from urban and rural areas across all three regions of Czechia. Twenty four-hour movement behaviour (sleep, sedentary behaviour, and physical activity) was monitored using ActiGraph accelerometers placed on the non-dominant wrists of children and their parents for seven consecutive days. Children's adherence to the WHO guidelines was analysed using logistic regression analysis. 25.9% of girls and 26.7% of boys simultaneously met all three 24-h movement behaviour guidelines (sleep + sedentary + physical activity), and 44.7% of girls and 46.1% of boys met any combination of two of the three guidelines, regardless of the children's gender, weight, or calendar age. Maternal overweight/obesity significantly (P = .05) decreased the odds of children achieving at least two of the three guidelines, while parental university education and maternal adherence to at least two of the three guidelines significantly (P = .05) increased the odds of children complying with these guidelines. Parents, especially mothers, play an important role in influencing their children in meeting 24-h movement behaviour guidelines and in shaping a healthy lifestyle.
Keywords: dospělí; Guideline Adherence; Sedentary Behavior; Female; předškolní dítě; dítě; Adult; ženské pohlaví; sedavý životní styl; průřezové studie; lidé; cvičení; rodiče; Parents; matky; spánek; Male; Cross-Sectional Studies; Czech Republic; Mothers; Child, Preschool; Sleep; Česká republika; Child; mužské pohlaví; Exercise; dodržování směrnic; Humans